Educación para la salud en adolescentes embarazadas para potenciar su salud mental en el Hospital de Zamora. - Loarte Quezada, Rosa María (2015)
In the present research work, it was pretended to design a health education program for pregnant teenagers; through the determination of risk factors for their health; protective factors with teenagers who attended to Zamora Hospital between January to June 2015 period. This thesis work is a qualitative-quantitative descriptive type, with a population of 25 teenagers to whom there were applied data collecting instruments through home visit, whose risk factors are the beginning of sexual intercourse before the 15 years old without protection, the presentation of anemia during gestation, fear of having complications during pregnancy and childbirth added to the few knowledge about pregnancy, birth, from the protective factors for the health of the study group it was found that they count with affective and economic support of their families, with a clear life project willing to continue with their studies and perform their mother role. With this reality it was proceeded to elaborate the health education program favoring in a positive way to maximize the mental health of pregnant teenagers. Key words: teenage pregnancy, mental health, health education